ANALISIS PENGARUH EKSPOR INDUSTRI MANUFAKTUR PADA KINERJA MAKROEKONOMI INDONESIA - Saimul, Saimul; Tambunan, M; Oktaviani, R; Firdaus, M (LPPM Universitas Terbuka, 2011)
The exports of manufacturing industry which consists of the export agroindustry and non-agroindustry, has an important role influencing the development of Indonesia's macroeconomic performance. This study aims to analyze the influence of manufacturing industry exports to Indonesia's macroeconomic performance. The study uses quarterly time series data from 1990 to 2009. Using VAR analysis model, the results of research are in short-term shocks to export agroindustry manufacturing has a positive effect on economic growth by 0.10%, but a negative effect on net exports, inflation, and exchange rates. Conversely, in the long term the shock has a negative effect on performance makrokonomi Indonesia. While the non-agroindustry export shocks in both the short and long term, has a positive effect on macroeconomic performance, except to the exchange rate has decreased in the long run.